2005
DOI: 10.2134/agronj2005.0085
|View full text |Cite
|
Sign up to set email alerts
|

Corn Stalk Nitrate Concentration Profile

Abstract: The end‐of‐season stalk nitrate test provides a method of assessing the N available to the corn (Zea mays L.) crop during the latter part of the season. This study was conducted to determine how stalk nitrate test results and interpretations are affected by sample composition. Stalks were collected from three field sites and separated into phytomers (node plus internode above), which were subdivided into three or five segments after length was measured. Nitrate‐N concentration of phytomers decreased linearly f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
26
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(34 citation statements)
references
References 6 publications
7
26
0
1
Order By: Relevance
“…These differences reflect the accumulation of nitrate in the bottom of corn stalks when N is applied in excess of crop N needs (Hanway and Englehorn, 1958;Binford et al, 1990) and support the observation that CSNTs can be used as a tool to fine-tune N fertilizer management on a field-by-field basis. The results are also consistent with data shown in Wilhelm et al (2005) that showed a difference of 15% among samples taken 10 to 30 cm, 15 to 35 cm, and 20 to 40 cm aboveground, suggesting that a change in sampling method will require a change in critical concentration.…”
Section: Statistical Analysessupporting
confidence: 91%
See 2 more Smart Citations
“…These differences reflect the accumulation of nitrate in the bottom of corn stalks when N is applied in excess of crop N needs (Hanway and Englehorn, 1958;Binford et al, 1990) and support the observation that CSNTs can be used as a tool to fine-tune N fertilizer management on a field-by-field basis. The results are also consistent with data shown in Wilhelm et al (2005) that showed a difference of 15% among samples taken 10 to 30 cm, 15 to 35 cm, and 20 to 40 cm aboveground, suggesting that a change in sampling method will require a change in critical concentration.…”
Section: Statistical Analysessupporting
confidence: 91%
“…Their results suggested that the length of the sampled stalk could be reduced from 20 to 4 cm if the stalk sample was centered between 18 and 22 cm aboveground. Wilhelm et al (2005) evaluated the differences in NO 3 -N concentration in samples that were taken 5 cm higher and lower on the stalk than the original 15 to 35 cm and noted a difference of 15% among samples taken 10 to 30 cm, 15 to 35 cm, and 20 to 40 cm aboveground. They also tested the difference in NO 3 -N content of phytomers (node plus internode above) along the length of the stalk, and concluded that the phytomer closest to the soil had a concentration 35 to 40% greater than the 15 to 35 cm section, suggesting that a change in sampling method will require a change in critical concentration.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Nitrate concentration is measured in a specific section of the corn stalk late in the growing season, and can be used to identify if crop N supply was yieldlimiting, adequate or excessive (Murdock and Schwab 2004;Wilhelm et al 2005). Similarly, basal stem tissue sap nitrate concentration has been used as a measure of N status in cereal crops (Hoel 1999).…”
Section: Plant-based Diagnostic Testsmentioning
confidence: 99%
“…The test provides feedback in N status that can be used for assessing whether N management (i.e., N rate, timing, form, or method of application) was optimized or not in a given year. The high accuracy of the CSNT for diagnosing the N status of corn in the near-optimal and excessive categories has been confirmed in several studies conducted across the Midwest (Balkcom et al 2003;Brouder et al 2000;Wilhelm et al 2005;Yang 2000). The DAI has a high sensitivity for diagnosing the deficient or below-optimal N status of corn Hatfield et al 2008).…”
mentioning
confidence: 80%